Development of stable and conductive interface between garnet structured solid electrolyte and lithium metal anode for high performance solid-state battery. (1st February 2020) - Alexander, George V.; Indu, M.S.; Kamakshy, Selvajyothi; Murugan, Ramaswamy
Abstract: Dense garnet structured solid electrolytes exhibit great promise for lithium metal batteries owing to its high lithium ion conductivity, good mechanical and electrochemical properties. However, the rigid interfacial contact between garnet structured electrolyte and electrode stymie their practical application. In this study, we propose an effective strategy to improve the lithium wettability of Li6.28 Al0.24 La3 Zr2 O12 (LLZA) with graphite (G) or lithium niobate [LiNbO3 (LNbO)] buffer layer. Our experimental investigation reveals a significant decrease in metallic lithium (Li) - LLZA interface resistance from 1078 Ω cm 2 to 91 Ω cm 2 and 58 Ω cm 2  by the application of a thin LiNbO3 /graphite buffer layer, respectively. In addition, Li |G-LLZA-G| Li cell exhibits a stable lithium stripping/platting performance with small voltage hysteresis and endures a critical current density up to 750 μA cm −2 in comparison to Li|LNbO-LLZA-LNbO|Li and its counterpart (Li |LLZA| Li). As a proof-of-concept, we demonstrate a stable cycling performance of quasi -solid-state battery with surface modified LLZA (G-LLZA) as solid electrolyte, lithium metal as anode and LiNi0.33 Mn0.33 Co0.33 O2 (NMC) as cathode with an initial discharge capacity of 162 mA h g −1 (50 μA cm −2 ) and 149 mA h g −1 (100 μA cm −2 ) at room temperature (25 °C).